1991
DOI: 10.1007/bf00318185
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of actin-filament bundles in myoid cells, Sertoli cells, and tunica albuginea of rat and mouse testes

Abstract: Frozen sections of the rat and mouse testes were stained with either FITC-phalloidin or NBD-phallacidin and viewed with conventional fluorescence and confocal laser microscopes in order to demonstrate the arrangement of actin-filament bundles in myoid cells, Sertoli cells and tunica albuginea. Myoid cells are rich in actin-filament bundles crossing at right angles. These bundles running in different directions can also be visualized by means of electron microscopy. Nerve fibers occur in the vicinity of myoid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Similarly, the co-expression of different types of IF in the same cells has been referred to above. The coexpression of actin and desmin, considered to be abundant in myoid cells (Maekawa et al 1991), has also been reported by Schlatt et al (1993) in the peritubular boundary tissue of the monkey.…”
Section: Peritubular Tissuesupporting
confidence: 74%
See 1 more Smart Citation
“…Similarly, the co-expression of different types of IF in the same cells has been referred to above. The coexpression of actin and desmin, considered to be abundant in myoid cells (Maekawa et al 1991), has also been reported by Schlatt et al (1993) in the peritubular boundary tissue of the monkey.…”
Section: Peritubular Tissuesupporting
confidence: 74%
“…Immunohistochemical studies of these contractile cells in the testicular capsule, in some mammals, have shown that they contain a number of microfilaments (MF) and intermediate filaments (IF), such as actin (Santamaria et al 1990;Maekawa et al 1991), smooth muscle myosin and desmin (Paranko and Pelliniemi 1992) and vimentin, desmin, -smooth muscle actin and smooth muscle myosin (Middendorff et al 2002). Seminiferous tubules in all mammals are surrounded by boundary tissue that contains myoid or smooth muscle cells (Maekawa et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This is due in part to the complicated texture of the lamina propria of seminiferous tubules in the human testis. In the rat testis the peritubular tissue consists of only one layer of myoid cells, and therefore has been well investigated (CLERMONT, 1958;LACY and ROTBLAT, 1960;LEESON and LEESON, 1963;Ross, 1967;TOYAMA, 1977;VIRTANEN et al, 1986;MAEKAWA et al, 1991MAEKAWA et al, , 1995. The myofibroblasts of the ratt seminiferous tubules possess bundles of filaments (stress fibres) and express the cytoskeletal proteins desmin, a-smooth muscle actin and smooth muscle myosin (SKALLI et al, 1986;BENZONANA et al, 1988;SAPPING et al, 1990, for review).…”
Section: Discussionmentioning
confidence: 99%
“…This unique cell shape of a myofibroblast surrounding a human seminiferous tubule differs markedly from other myofibroblasts in the human genital tract, e. g. in the coat of the ductuli efferentes or of the ductus epididymidis (HOLSTEIN, 1969), in the tunica dartos (HOLSTEIN et al, 1974) and from testicular peritubular myoid cells of other species excluding some higher vertebrates and primates (CLERMONT, 1958;LACY and ROTBLAT, 1960;LEESON and LESSON, 1963;ROSS, 1967;CHRISTL, 1990;MAEKAWA et al, 1991;PALOMBI et al, 1992). The myoid nature of the cells of the lamina propria of the guinea pig, rat and human seminif erous tubules was earlier proved (GROSCHEL-STEWARD and UNSICKER, 1977;VIRTANEN et al, 1986;SKALLI et al, 1986;BENZONANA et al, 1988).…”
Section: Myofibroblastsmentioning
confidence: 93%
“…It has been established that hydrostatic pressure alone is not sufficient for the outflow of testicular fluid into and through the excurrent ducts, but that the testicular capsule and peritubular boundary tissue, comprising myoid or smooth muscle cells, play an important role in this regard (Banks et al, 2006;Hargrove et al, 1977;Middendorff et al, 2002). Smooth muscle cells have been indentified, ultrastructurally, immunohistochemically and pharmacologically in both the testicular capsule and peritubular boundary tissue of mammals (Banks et al, 2006;Maekawa et al, 1991Maekawa et al, , 1996Schlatt et al, 1993;Virtanen et al, 1986). Similarly, smooth muscle cell layers have been demonstrated in the periductal tissue in the rete testis, tubulus rectus, and ductus epididymidis of mammals (Dinges et al, 1991 Kasper andStosiek, 1989;Wakui et al, 1994).…”
Section: Introductionmentioning
confidence: 99%